2023
DOI: 10.1155/2023/4752502
|View full text |Cite
|
Sign up to set email alerts
|

Epiisopiloturine, an Alkaloid from Pilocarpus microphyllus, Attenuates LPS-Induced Neuroinflammation by Interfering in the TLR4/NF-κB-MAPK Signaling Pathway in Microglial Cells

Abstract: Neuroinflammation is present in the pathophysiological mechanisms of several diseases that affect the central nervous system (CNS). Microglia have a prominent role in initiating and sustaining the inflammatory process. Epiisopiloturine (EPI) is an imidazole alkaloid obtained as a by-product of pilocarpine extracted from Pilocarpus microphyllus (jaborandi) and has shown promising anti-inflammatory and antinociceptive properties. In the present study, we investigated the effects of EPI on the inflammatory respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…This suggests that immune stimulation with LPS/S/NO 2 enhances nitrate biosynthesis from nitric oxide and nitrite oxidation and, probably, from organic precursors such as S-nitroso thiols and L-arginine through the nitric oxide synthase pathway. In fact, it has been evidenced that immune activation of TLR4 results in marked induction of nitric oxide synthase and nitrite production in microglial cells [ 39 , 40 ] and macrophages [ 41 ] in culture.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that immune stimulation with LPS/S/NO 2 enhances nitrate biosynthesis from nitric oxide and nitrite oxidation and, probably, from organic precursors such as S-nitroso thiols and L-arginine through the nitric oxide synthase pathway. In fact, it has been evidenced that immune activation of TLR4 results in marked induction of nitric oxide synthase and nitrite production in microglial cells [ 39 , 40 ] and macrophages [ 41 ] in culture.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cells in the brain, predominantly microglial, monitor the physiological environment of the brain. When stimulated by external pathological factors, the activated microglial cells lead to excessive release of proinflammatory cytokines including IL-1β, IL-6, and TNF-α through downstream signaling pathways, resulting in neuroinflammation (de Sousa et al, 2023;Ni et al, 2023). This neuroinflammation may affect cell proliferation, differentiation, neuronal activity, and neuronal network and is closely associated with cognitive function (Palmisano et al, 2022;Yildirim et al, 2023).…”
Section: Melatonin Improved Msd-induced Inflammation In the Hippocampusmentioning
confidence: 99%
“…With the continuous aging of the global population, the incidence and prevalence of NDs are increasing, so it is urgent to study effective prevention and treatment strategies. Recent studies have found that neuroinflammation and microglia play crucial roles in the development and progression of NDs (de Sousa et al, 2023). Microglia can polarize into M1 and M2 phenotypes, which exert pro-inflammatory and anti-inflammatory effects, respectively in neuroinflammation, thereby exerting protective or toxic effects on neuronal cells (Orihuela et al, 2016).…”
Section: Introductionmentioning
confidence: 99%